A new species of the genus Empitrombium Southcott, 1994 (Acari: Microtrombidiidae) from Turkey - Sevsay, Sevgi̇; Karakurt, İbrahim (Zootaxa, 2013)
A new species, Empitrombium makolae sp. nov., is described based on active postlarval forms and larvae obtained from adult females kept in the laboratory. Based on the adult morphology of E. makolae, the adult life stage of Platytrombidium littorale (Michener 1946) is moved back to the genus Empitrombium. A key to species of Empitrombium is provided.